Academic detailing as a method to improve general practitioners’ drug prescribing in type 2 diabetes: evaluation of changes in prescribing - Harald Christian Langaas; Øyvind Salvesen; Roar Dyrkorn; Hege Salvesen Blix; Olav Spigset (Scandinavian Journal of Primary Health Care, 2023)
AbstractObjective To investigate the effect of an academic detailing intervention on the utilisation of type 2 diabetes medication among general practitioners.Design We developed an academic detailing campaign based on the revised national treatment guideline for diabetes and the best available evidence. General practitioners were offered a 20-minute one-to-one visit by a trained academic detailer.Setting and subjects A total of 371 general practitioners received a visit and represented the intervention group. The control group consisted of 1282 general practitioners not receiving a visit.Main outcome measures Changes in prescribing from 12 months before to 12 months after the intervention. The primary endpoint was a change in metformin. Secondary endpoints were changes in other groups of Type 2 diabetes medication and of these drugs in total.Results Prescribing of metformin increased by 7.4% in the intervention group and 5.2% in the control group (p = .043). Sodium-glucose cotransporter-2 inhibitors increased by 27.6% in the intervention group and 33.8% in the control group (p = .019). For sulfonylureas there was a decrease of 3.6% in the intervention group vs. 8.9% in the control group (p = .026). The total amount of prescribed medications for type 2 diabetes increased by 9.1% in the intervention group and 7.3% in the control group (p = .08).Conclusion Academic detailing initiated a small but statistically significant increase in the prescription of metformin. For a complex subject like type 2 diabetes, we recommend reserving more time in the visit than the 20 min our campaign aimed for.